Pengaruh Peran Perawat sebagai Edukator dalam Melakukan Perawatan Luka di Rumah Sakit Royal Prima Medan - Patimah Sari Siregar; Eva Latifah Nurhayati; Benediktus Giawa; Mitasari Manalu; Yurni Laia (Malahayati Nursing Journal, 2022)
ABSTRACT The job of teachers is that medical caretakers help clients in expanding the degree of wellbeing information, side effects of sickness and even activities given, so there is an adjustment of the way of behaving of the client after wellbeing training is completed. (Arif Rahman, Carla Raymondalexas Marchira, and Ibrahim Rahmat, 2016). Wound is an interruption of typical states of the skin or harm to the congruity of the skin, mucous layers and bones or other body organs, the reason for wound care is to give a satisfactory climate to wound mending, retention of waste, strain and immobilization of wounds, keeping wounds and new epithelial tissue from injury. precisely, keeping the injury from bacterial defilement, expanding hemostasis by squeezing the dressing, giving mental and actual solace to the patient (Ismail, 2020). The motivation behind this study was to decide the impact of the attendant's job as a teacher in performing twisted care at the Regal Prima Medical clinic Medan 2021. The plan of this review utilized a pre-trial plan with a one gathering pre-test post-test plan. Tests were taken utilizing a complete examining of 25 individuals. Gathering information utilizing a poll sheet. Information investigation utilized the Wilcoxon sign position test with a meaning of 0.05. The consequences of the Wilcoxon sign position test in the end-product got a p esteem = 0.000 = 0.05 so it very well may be reasoned that there is an effect on the job of attendants as teachers in completing injury care at the Regal Prima Clinic Medan. Ideas for additional specialists can analyze the impact of the job of attendants as teachers in postoperative patients. Keywords: Role of Nurses; Educator; Injury Cure  ABSTRAK Peran Edukator (pendidik) adalah petugas medis membantu klien dalam memperluas informasi tingkat kesejahteraan, efek samping penyakit bahkan aktivitas yang diberikan, sehingga ada penyesuaian cara berperilaku klien setelah sekolah kesejahteraan dilakukan. Luka adalah gangguan keadaan khas kulit atau kerusakan perkembangan kulit, selaput lendir dan tulang atau organ tubuh lainnya, alasan perawatan luka adalah untuk memberikan iklim yang cukup untuk memperbaiki luka, menelan rembesan, ketegangan dan imobilisasi. luka, menjaga luka dan jaringan epitel baru dari cedera. mekanis, menjaga cedera dari pencemaran bakteri lebih lanjut mengembangkan hemostasis dengan meremas balutan, memberikan pelipur lara mental dan aktual kepada pasien. Alasan penelitian ini adalah untuk mengetahui dampak dari pekerjaan tenaga medis sebagai pengajar dalam melakukan perawatan terpelintir di Klinik Gawat Darurat Imperial Prima Medan 2022. -rencana tes. Pengujian dilakukan dengan menggunakan pemeriksaan menyeluruh dari 25 orang. Mengumpulkan informasi menggunakan lembar jajak pendapat. Penyelidikan informasi menggunakan uji posisi tanda Wilcoxon dengan makna 0,05. Hasil uji posisi tanda Wilcoxon pada produk akhir didapatkan p esteem = 0,000 = 0,05 sehingga dapat dimaklumi bahwa ada pengaruh pekerjaan tenaga medis sebagai guru dalam melakukan perawatan terpelintir di Klinik Regal Prima Medan. Gagasan untuk ilmuwan tambahan dapat menganalisis dampak pekerjaan petugas medis sebagai guru pada pasien pasca operasi. Kata Kunci : Peran Perawat; Edukator; Perawatan luka.